Blunt cerebrovascular injury of cervical and petrous ICA with stroke: A case study. (June 2022) - Gorji, Leva; Narayanan, Ragavan; Siebenburgen, Christa
Abstract: This case report documents treatment of a 32-year-old male patient after being extricated from an extensively damaged motor vehicle after a collision. On first presentation, the patient had a Glascow Coma Score of 14 and a pan-scan revealed a severely comminuted fracture of the proximal left femoral shaft, a fracture of the left patella, and multiple rib fractures. A neurological exam on a later evaluation showed global aphasia and sharp decline in movements of the right upper and lower extremities even with painful stimuli. A CT Angiography of the head and neck was obtained and revealed evidence of occlusion in the upper cervical segment and proximal petrous segment of the left internal carotid artery (ICA). Two 6x40mm precise stents were placed restoring normal intracranial flow to the patient's left ICA. The patient was discharged having sensation and motor function in all extremities and with resolved aphasia and no neurologic deficits.